On the reserves of the infant mortality reduction in Russia - A.A. Baranov; V.Yu. Albitsky; A.G. A.G. Ilyin ("Paediatrician" Publishers LLC, 2006)
(Voprosy sovremennoi pediatrii = Current pediatrics. 2006; 5 (5): 5-7)